The efficiency of treatment with a combined chondroitin sulfate and glucosamine hydrochloride drug for knee and hip osteoarthritis: intermediate results of a Russian observational study - A. M. Lila; L. I. Alekseeva; K. A. Telyshev; A. A. Baranov; E. A. Trofimov (Современная ревматология, 2020)
Objective: to assess pain dynamics, daily functional activity of joints, quality of life, and treatment satisfaction in patients with knee and hip osteoarthritis (KOA and HOA), who long take a combined glucosamine (GA) and chondroitin sulfate (CS) drug in routine clinical practice.Patients and methods: An interim analysis of data from an open multicenter prospective non-interventional study that is being conducted in the Russian Federation was carried out. The study included patients with Kellgren–Lawrence Stages I–III KOA or HOA, who were treated with a combined GA and CS drug (Theraflex®). The interim analysis was based on the data obtained at 16–24 weeks of treatment (Visit 2) in 542 patients (50% of the total sample).Results and discussion. A study group included patients with KOA (n=399) or HOA (n=143) from 43 centers in Russia. At visit 2, the KOA/HOA patients showed positive changes in all subscales of the Knee disability and Osteoarthritis Outcome Score (KOOS/Hip disability and Osteoarthritis Outcome Score (HOOS) questionnaires compared to the baseline level. The proportion of patients with a ≥20% increase in different subscale scores ranged from 42.6 to 67.4% for KOA and from 47.6 to 66.4% for HOA.Most (89.1%) patients took Theraflex® for ≥3 months. 76,1% of patients were satisfied with treatment efficiency. Adverse events (AEs) related to treatment were recorded in 16 (3.0%) patients and included mainly gastrointestinal tract disorders in 12 (2.2%) cases.Conclusion. The results obtained at 16–24 weeks of Theraflex® treatment are indicative of a decrease in the frequency and intensity of pain and other symptoms of OA, as well as increases in joint functional activity and quality of life in patients with KOA or HOA after the first cycle of therapy. The majority of the patients were satisfied with the treatment. The incidence of drug-related AEs was low, while their nature was consistent with information on the drug's side effects.